Land and forest rights in the Chittagong hill tracts - Roy, Raja Devasish (Kathmandu, 2002)
This discussion paper provides a sharp focus on competing claims and differentiated interpretations to land and forest rights in the Chittagong Hill Tracts of Bangladesh. The paper provides a historical perspective of the fallout of armed conflict on people and natural resources, and moves to capture the opportunities made available by the peace accord of 1997 in Bangladesh and the implications for competing interests related to livelihood-based resources that are manifested in the region in conflicts over land and forest rights. The author concludes that a comprehensive policy related to land and natural resources is imperative to ensure equitable and environmentally sound resource use practices in the Chittagong Hill Tracts of Bangladesh.
Keywords: Forest and forestry-Bangladesh